74 Fatal drowning in Indonesia: Understanding the gap of knowledge through scoping review. (20th November 2022) - Cenderadewi, Muthia; Franklin, Richard; Devine, Susan; Sari, Dian Puspita
Abstract : Background: Little is known about unintentional drowning deaths in Indonesia, the world's fourth most populous country and largest archipelagic state, where high numbers of meteorological and hydrological events including disasters occur annually. Aims: To identify gaps in the research knowledge base on the epidemiology and risk factors of unintentional drowning deaths, and to examine the types of evidence that inform downing prevention in Indonesia within a socio-ecological health promotion framework. Methods: A scoping review, guided by PRISMA, was conducted to locate all relevant studies published between 2005 and 2022 on 8 databases (MEDLINE (Ovid), CINAHL, Informit Health Collection, PsycINFO (ProQuest), Scopus, SafetyLit, BioMed Central, and Google Scholar), and Indonesian journal databases, government agencies and organisations websites. Results: Limited publications on drowning rates, risk factors, and prevention of drowning were observed within Indonesia between 2005 and 2022. The only source of data for drowning deaths identified in this review were derived from autopsy records, underlining the possibility of underrepresentation of drowning data in Indonesia. The under-investigated measurement of association between various exposures and drowning incidents in Indonesia was apparent. The over-reliance on individual-focused, behaviour-based preventive measures was observed in Indonesia, with a marked under-development of a broader socio-ecological approach of health promotion to drowning prevention. Conclusion: Further research focusing on developing drowning prevention measures aligned with the concept of the health promotion framework, which suggests integrating educational, behavioural, socio-environmental, and regulatory approaches, is imperative. Learning outcome: Participants will be able to analyse the gap of drowning prevention available in Indonesia